Tibial plateau fractures (AO type B3) combined with tibial tubercle fracture: Case report and review of the literature. Issue 36 (September 2018) - Tan, Lei; Li, Yan-Hui; Li, Yuying; Lin, Tong; Zhu, Dong; Sun, Da-Hui
Abstract: Rationale: Tibial tuberosity fractures most often occur in the adolescents. Fracture of tibial tuberosity in adults is extremely rare with only 5 reported cases till date. Tibial plateau fractures combined with tibial tubercle fractures are not common. Patient concerns: We report here a type B3 tibial plateau fracture (AO classification) with a concomitant fracture of tibial tuberosity. Diagnoses: Anteroposterior and lateral knee view radiographs revealed a complex comminuted fracture of the right tibial plateau (AO Type B3; Schatzker Type IV) with tibial tubercle fracture. Three-dimensional computed tomography (CT) showed that the tibial media plateau was split into 2 pieces in the sagittal plane, along with the isolated tibial tubercle. Interventions: The open procedure was performed first and a standard posteromedial approach for medial and posteromedial tibial plateau fracture was used with double locking plate fixation. The tibial tuberosity was fixed with a cortical screw. Outcomes: The patient showed full range of motion in right knee after 8 weeks. The patient was allowed full weight bearing at 4 months. Eight months after operation, he was asymptomatic, showed a full range of motion and good strength. He had returned to work with no limitations. Lessons: Fractures of the partial tibial plateau combined with tibial tubercle are present and should not be ignored. Accurate diagnosis and proper treatment will help achieve favorable outcomes in these patients.